Research on Spur Gear Profile Modification Based on Stiffness of the Elastohydrodynamic Lubrication Friction Pair - Xia Boqian; Zhang Yinghao; Zhang Zebin (Jixie chuandong)
The influence of elastohydrodynamic lubrication (EHL) to the spur gear profile modification is considered for the first time, and a new method of spur gear profile modification is proposed using gear EHL friction pair meshing stiffness to replace gear meshing stiffness to calculate the maximum modification amount. Based on the EHL theory and by simplifying the EHL film into linearized spring and damping, a tribology-dynamics coupling model of line contact friction pair is established and the stiffness of tooth surface EHL friction pair is obtained by numerical method; the gear meshing stiffness and the meshing stiffness of gear EHL friction pair are calculated respectively using the definition of ISO gear meshing stiffness and the maximum modification amount is calculated based on two different gear meshing stiffness; through Creo, the meshing models of a standard gear pair, an ISO method modified gear pair and an EHL friction pair stiffness modified gear pair are established respectively. Dynamic meshing force, angular acceleration and transmission error of the three kinds of gear pairs are simulated and compared using Adams and Romax. The values of maximum modification amount calculated based on the stiffness of the EHL friction pair are compared with the values of modification amount of some engineering actual modified gears. The results show that the gear stiffness decreases significantly when taking into account the effect of EHL, which leads to an increase in the maximum gear modification amount. The modification effect based on the stiffness of the EHL friction pair is better than that when using the ISO method and the gear dynamic performance and transmission performance is improved significantly. And the theoretical calculation values of the modification amount are also closer to the values of actual modification amount of the engineering gear.